Sexual risk behaviour and viral suppression among HIV-infected adults receiving medical care in the United States - Mattson, Christine L. (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: To describe the prevalence and association of sexual risk behaviours and viral suppression among HIV-infected adults in the United States. DESIGN: Cross-sectional analysis of weighted data from a probability sample of HIV-infected adults receiving outpatient medical care. The facility and patient response rates were 76 and 51%, respectively. METHODS: We analysed 2009 interview and medical record data. Sexual behaviours were self-reported in the past 12 months. Viral suppression was defined as all viral load measurements in the medical record during the past 12 months less than 200 copies/ml. RESULTS: An estimated 98 022 (24%) HIV-infected adults engaged in unprotected vaginal or anal sex; 50 953 (12%) engaged in unprotected vaginal or anal sex with at least one partner of negative or unknown HIV status; 23 933 (6%) did so while not virally suppressed. Persons who were virally suppressed were less likely than persons who were not suppressed to engage in vaginal or anal sex [prevalence ratio, 0.88; 95% confidence interval (CI), 0.82–0.93]; unprotected vaginal or anal sex (prevalence ratio, 0.85; 95% CI, 0.73–0.98); and unprotected vaginal or anal sex with a partner of negative or unknown HIV status (prevalence ratio, 0.79; 95% CI, 0.64–0.99). CONCLUSION: The majority of HIV-infected adults receiving medical care in the U.S. did not engage in sexual risk behaviours that have the potential to transmit HIV, and of the 12% who did, approximately half were not virally suppressed. Persons who were virally suppressed were less likely than persons who were not suppressed to engage in sexual risk behaviours.